2020
DOI: 10.1021/acssensors.0c01250
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Label-Free Detection of the Measles Virus Using an N-Heterocyclic Carbene-Based Electrochemical Biosensor

Abstract: With the current intense need for rapid and accurate detection of viruses due to COVID-19, we report on a platform technology that is well suited for this purpose, using intact measles virus for a demonstration. Cases of infection due to the measles virus are rapidly increasing, yet current diagnostic tools used to monitor for the virus rely on slow (>1 h) technologies. Here, we demonstrate the first biosensor capable of detecting the measles virus in minutes with no preprocessing steps. The key sensing elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…In recent work, Birss and co-workers have demonstrated the use of an NHC decorated Au electrode for the electrochemical detection of the measles virus. [50] The NHC is covalently bonded to the measles antibody, creating a monolayer. The system is then used as an electrochemical biosensor.…”
Section: Miscellaneousmentioning
confidence: 99%
“…In recent work, Birss and co-workers have demonstrated the use of an NHC decorated Au electrode for the electrochemical detection of the measles virus. [50] The NHC is covalently bonded to the measles antibody, creating a monolayer. The system is then used as an electrochemical biosensor.…”
Section: Miscellaneousmentioning
confidence: 99%
“…For example, recent reports have employed thiol-based ligands to develop patterned molecular films for site-specific immobilization of biomolecules, , to investigate host–guest complexation for surface detection of polycyclic aromatic hydrocarbons, and to tether aptamers on implantable electrochemical devices for in vivo diagnostics. , In 2014, Crudden and co-workers reported that N -heterocyclic carbene (NHC) ligands form stable, well-ordered, and self-assembled monolayers on crystalline gold that can, in many situations, exceed the performance of thiols. Since their initial work, multiple research groups have explored the capabilities of NHC-coated surfaces toward a variety of applications. …”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, the application of antibody fragments seems to be a very promising approach for the development of sensors for the determination of virus proteins because it enables increasing the surface concertation of sites that are selective to virus proteins [125,126] There are some other researches dedicated to the development of biosensors with the potential application for the determination of SARS-CoV-2 infection, based on the antigen-antibody interactions. In order to exploit such interactions, an electrochemical biosensor based on electrode covered with a SAM and specific-antibodies against SARS-CoV-2 proteins, was designed [127].…”
Section: Ellipsometry and Spr Based Immunosensorsmentioning
confidence: 99%